Antiphospholipid Syndrome and Pregnancy - Grabowska, Ewa; Pawłocik, Weronika; Pawlak, Weronika; Wojtala, Laura; Szymańska, Julia; Kapłon, Kamil; Możdżyńska, Agnieszka; Musiał, Lena; Rymarz, Anna; Kamińska, Izabela (Journal of Education, Health and Sport, 2023)
Antiphospholipid syndrome is an autoimmune disease with a wide spectrum of manifestations from different organs, therefore it is challenging to diagnose. The disease presents antiphospholipid antibodies such as anticardiolipin antibodies (aCL), lupus anticoagulant (LA) and antiβ2-glycoprotein 1 antibodies (β2GPI). The most common symptoms include thrombosis in veins and arteries and obstretical complications such as early miscarriage, intrauterine fetal death, intrauterine growth restriction (IUGR), placental insufficiency, premature labor and eclampsia. To diagnose a patient with APS certain criteria have been chosen, where at least one clinical and one laboratory criterion must be present. In many cases it takes a lot of time before a proper diagnosis has been made, when a female patient presents obstretical complications. Adequate pharmacological treatment increases the odds of live birth rate from 20-30% to 70-80%. Scientific research shows correlation between antiphospholipid syndrome, infertility and premature ovarian insufficiency. Treatment mostly consists of heparin and low-dose aspirin, in certain cases hydrochloroquine is prescribed. Aside from pharamcological therapy, it is very important to minimize the effects of modifiable risk factors. The following article focuses on complications, diagnosing and therapy in pregnant women suffering from Antiphospholipid syndrome. All sources can be found in Pubmed’s website database.